CompTIA A+ certification all-in-one for dummies - Clarke, Glen E. (--For dummies., 2012)
Comprehensive coverage of everything you must know to pass CompTIA's A+ exam A+ is the gateway certification into many IT careers, and interest in certification is exploding. This bestselling A+ certification guide is updated to cover the new A+ exam. It includes the new Windows coverage and reflects the revised emphasis on objectives. Nine minibooks focus individually on specific hardware and OS characteristics including installation and configuration, diagnostics, preventive maintenance, motherboard and processors, printers, networking, and fundamentals.